2005
DOI: 10.1152/ajpgi.00575.2004
|View full text |Cite
|
Sign up to set email alerts
|

The histone deacetylase inhibitor butyrate downregulates cyclin B1gene expression via a p21/WAF-1-dependent mechanism in human colon cancer cells

Abstract: Histone deacetylase (HDAC) inhibitors are showing promise as treatment for a variety of human cancers, but their precise mechanism of action has not been elucidated. We examined the effects of the HDAC inhibitor butyrate on colon cancer cells, focusing on its effect on the cell cycle promoter cyclin B(1). In HT-29 cells, sodium butyrate-mediated growth inhibition is associated with a marked decrease in cyclin B(1) mRNA levels. The decrease in cyclin B(1) occurred in a delayed fashion (at 24 h), is completely b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 44 publications
2
44
0
Order By: Relevance
“…NaBu and other SCFAs are naturally occurring products produced by fiber fermentation in the colon and have been found to inhibit the growth of colon cancer cells both in vivo and in vitro (38). In addition, when SCFAs were applied in combination with a variety of chemotherapy drugs, better co-treatment efficacy was noted.…”
Section: Discussionmentioning
confidence: 99%
“…NaBu and other SCFAs are naturally occurring products produced by fiber fermentation in the colon and have been found to inhibit the growth of colon cancer cells both in vivo and in vitro (38). In addition, when SCFAs were applied in combination with a variety of chemotherapy drugs, better co-treatment efficacy was noted.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the critical role of p21 induction for mediating HDACi-induced growth arrest in colon cancer cells is demonstrated by the attenuated growth inhibitory effect of HDACi on p21 deficient HCT116 cells. 70 In addition to p21, HDACi also induce expression of several other growth inhibitory proteins including p15INK4b, 92 p16 86 and GADD45α and ÎČ 93 Notably, HDACi also downregulate expression of several pro-proliferative genes including c-myc, 94,95 cyclin B1 96 and cyclin D1 97 in colon cancer cells. In contrast to p21 however, the relative importance of these effects in mediating HDACi-induced growth arrest, have not been directly tested.…”
Section: Growth Arrestmentioning
confidence: 99%
“…[4][5][6] NaB-mediated cell cycle withdrawal of CRCs appears to be dependent on acetylation of histones and consequent changes in transcription, requiring continuous protein synthesis and the expression of p21. 7 It has recently been shown that 1 mM NaB is the best working concentration to activate the differentiation program in CRCs without triggering apoptosis, whereas 5 mM NaB is sufficient to induce a p53-independent apoptotic cell death by activating a pathway involving p38, PPARg and caspases. 6,8 Several intracellular signaling cascades have been implicated in the regulation of the proliferation-differentiation balance in enterocytes by the coordinated expression of the genome in response to environmental cues.…”
mentioning
confidence: 99%